2015
DOI: 10.1002/stc.1810
|View full text |Cite
|
Sign up to set email alerts
|

Linear dynamic analysis and active control of space prestressed taut cable net structures using wave scattering method

Abstract: Summary In this paper, the linear dynamic analysis and active control of prestressed taut cable net structures are investigated by the wave scattering method. Wave motion equations of cables are firstly derived to obtain the wave dispersion characteristics, which are the combinations of the longitudinal tensile wave equations of bars and transverse wave equations of taut strings. The waveguide and scattering matrices of cables are then formed by the force balance and displacement boundary conditions. The deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Here, it is assumed that all cables are tensioned so that the cable-frame structure can be considered as a weakly nonlinear system. According to the reference Wang and Li (2016), the wave motion of a cable consists of the longitudinal motion (Line 2) and the transverse wave motion (Line 3). It can be seen from the wave motion equations that the longitudinal stiffness and the transverse stiffness of a cable are mainly determined by their elongation rigidity and instantaneous tensions, respectively.…”
Section: Exact Dynamic Response Analysis For Cable-frame Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it is assumed that all cables are tensioned so that the cable-frame structure can be considered as a weakly nonlinear system. According to the reference Wang and Li (2016), the wave motion of a cable consists of the longitudinal motion (Line 2) and the transverse wave motion (Line 3). It can be seen from the wave motion equations that the longitudinal stiffness and the transverse stiffness of a cable are mainly determined by their elongation rigidity and instantaneous tensions, respectively.…”
Section: Exact Dynamic Response Analysis For Cable-frame Structuresmentioning
confidence: 99%
“…In recent years, as large, light, flexible structures have been widely used in aerospace field (Renno and Mace, 2014; Sun et al, 2020), modal control has shown distinct disadvantages, and wave control has gained widespread attention for some complex and large structures. Wang and Li (2016) investigated the linear dynamic behavior and active control of cable net structures based on a wave scattering method. It has been argued that high levels of cable pretension can mitigate large initial deflections, rendering the system sufficiently stiff with the cable net structure for outer space applications being considered a weakly nonlinear system.…”
Section: Introductionmentioning
confidence: 99%